Professional athletes' shrinking privacy boundaries : fans, information and communication technologies, and athlete monitoring - Sanderson, Jimmy (London : Human Kinetics, Inc., 2009)
This case study considers how audience labor performed via information and communication technologies (ICTs) helps sports organizations monitor professional athletes. Three incidents are examined--(a) National Basketball Association (NBA) player Greg Oden participating in a pickup (casual) basketball game while he was rehabilitating an injured knee, (b) photographs posted on the Internet that captured National Football League player Matt Leinart posing with several young women in a hot tub and holding a beer bong, and (c) a video posted on YouTube that depicted NBA player Josh Howard disparaging the U.S. national anthem. The case study explores how ICTs enable sports organizations to capitalize on free labor provided by audience members to intensify surveillance of professional athletes and how fans' ability to comment on news coverage of these stories reinforces organizational control, further reifying professional athletes as commodities.
Originally published in Sanderson, J. (2009). Professional athletes' shrinking privacy boundaries: Fans, information and communication technologies, and athlete monitoring. International Journal of Sport Communication, 2(2), 240-256. DOI:.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Oden, Greg; Leinart, Matt; Howard, Josh, -- active 2009.; National Basketball Association; National Football League; Privacy